Pinkalicious : story time - Kann, Victoria (New York : Harper, an imprint of HarperCollinsPublishers, 2016)
After Pinkalicious meets her favorite author, she is inspired to write her own stories and can't wait to use her imagination in a school writing festival.
Keywords: Authorship -- Fiction; Imagination -- Fiction; Pink -- Fiction